Recent advances and applications of molecularly imprinted polymers in solid‐phase extraction for real sample analysis. Issue 1 (9th January 2021) - Hu, Tianliang; Chen, Run; Wang, Qiang; He, Chiyang; Liu, Shaorong
Abstract: Sample pretreatment is essential for the analysis of complicated real samples due to their complex matrices and low analyte concentrations. Among all sample pretreatment methods, solid‐phase extraction is arguably the most frequently used one. However, the majority of available solid‐phase extraction adsorbents suffer from limited selectivity. Molecularly imprinted polymers are a type of tailor‐made artificial antibodies and receptors with specific recognition sites for target molecules. Using molecularly imprinted polymers instead of conventional adsorbents can greatly improve the selectivity of solid‐phase extraction, and therefore molecularly imprinted polymer‐based solid‐phase extraction has been widely applied to separation, clean up and/or preconcentration of target analytes in various kinds of real samples. In this article, after a brief introduction, the recent developments and applications of molecularly imprinted polymer‐based solid‐phase extraction for determination of different analytes in complicated real samples during the 2015‐2020 are reviewed systematically, including the solid‐phase extraction modes, molecularly imprinted adsorbent types and their preparations, and the practical applications of solid‐phase extraction to various real samples (environmental, food, biological, and pharmaceutical samples). Finally, the challenges and opportunities of using molecularly imprinted polymer‐based solid‐phase extraction for real sample analysis are discussed.